The Effects of Hybridization and Parasite Infection on the Survival and Behaviour of Endangered Landlocked Salmon Subject to Predation : Implications for Genetic Rescue - Eronen, Aslak; Janhunen, Matti; Hyvärinen, Pekka; Kortet, Raine; Karvonen, Anssi (Evolutionary Applications)
A prerequisite of genetic rescue in endangered and genetically depauperate populations is to pre-evaluate between possible pros and cons of hybridization for the life history and survival of the target population. We hybridized the critically endangered Saimaa landlocked salmon (Salmo salar m. sebago) with one of its geographically closest relatives, anadromous Baltic salmon from River Kymijoki. In two similar experiments, conducted in semi-natural streams during overwintering (at age 1.5) and in early summer (age 2+), we studied how hybridization and eye parasite infection (Diplostomum pseudospathaceum) affected survival from predation by Northern pike (Esox lucius). Additionally, we recorded movements of the juvenile salmon using passive integrated telemetry to gain insights into the effect of hybridization and infection on antipredatory behaviour (movement activity and habitat use). Among the uninfected groups, we found significantly lower mortality of hybrid salmon (mortality ± S.E. 14.5% ± 5.4%) compared to purebred landlocked salmon (37.2% ± 9.4%), supporting a positive effect of hybridization under predation risk. This benefit, however, was cancelled out by the parasite infection, which impaired vision and increased the susceptibility to predation. The negative effects of infection were particularly pronounced in the anadromous salmon due to lower infection resistance, compared to the landlocked salmon. Hybridization per se did not affect the activity levels of salmon, but overwintering activity correlated positively with eye cataract coverage, and summer activity was highest in anadromous salmon. These results demonstrate that controlled supplementation of a small animal population with genetically more diverse hybrids could entail both positive and negative implications, at least in the first crossbred generation. 2024